Highly Stable and Reproducible Biosensor Interface based on Chitosan and 2,5-Di(thienyl)pyrrole based Conjugated Polymer - Ozkan, Betul Cicek; Soganci Aras, Tugba; Turhan, Huseyin; Ak, Metin (Elsevier Science Sa, 2022)
Interface design is the most crucial part of biosensor development because its rational design methodologies are directly related to the quality of sensing performance, such as sensitivity, reproducibility, stability, and linearity. In this study, a thienyl pyrrole derived electroactive monomer [N-1, N-4-bis(2,5-di(thiophene-2-yl)-1H-pyrrol-1-yl) terephthalamide] (TP) has been synthesized and electropolymerized onto chitosan (CS) and chitosan-reduced graphene oxide (rGO) modified electrode to produce highly stable and reproducible sensor platforms for glucose detection. The synergistic interactions of chitosan and p(TP) have produced the sensor platform inherent properties such as conductivity in three dimensions, ability to covalently bind the enzyme, interface compatibility of components, hydrophilicity. CS/p(TP)/GOx bioelectrodes offer higher sensitivity (0.322 mu A mu M-1 cm(-2)), detection limit (0.097 mu M) and good selectivity compared to CS-rGO/p(TP)/GOx (0.531 mu A mu M-1 cm(-2) and 0.159 mu M) bioelectrodes. Also, CS/p(TP)/GOx bioelectrodes show excellent longer-term storage stability, retaining 98.6% sensitivity after nine weeks, whereas the CS-rGO/p(TP)/GOx bioelectrode lost initial activity in two weeks when stored at 4 ?. Aside from the excellent stability and sensitivity, multiple sensor electrodes prepared under the same conditions gave the same glucose response without needing to be recalibrated.
Keywords: Glucose biosensor; Chitosan; Conducting polymer; rGO